Anatomical correlates of visual and tactile extinction in humans: a clinical CT scan study. Issue 4 (April 1994) - Vallar, G; Rusconi, M L; Bignamini, L; Geminiani, G; Perani, D
Abstract : The anatomical correlates of tactile and visual extinction with double simultaneous stimulation were investigated in a series of 159 patients with right brain damage caused by stroke. Forty six patients showed extinction (22 tactile, 14 visual, 10 tactile and visual). Over 50% of the patients with extinction had deep lesions, which were found in about 25% of the patients with visuospatial neglect not associated with extinction. In the patients with extinction and cortico-subcortical damage the paraventricular occipital white matter and the dorsolateral frontal cortex were most often involved. By contrast, when neglect was also present, the lesions clustered in the inferior parietal lobule. These data suggest, from an anatomical perspective, that partly different neural mechanisms may underlie neglect and extinction. The comparatively high frequency of subcortical lesions involving the ascending pathways may be a neural correlate of a sensory component of extinction.